PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR EKONOMI KELAS X SMA SANTA MARIA NANGA PINOH - Epensius, Epensius; Genjik, Bambang; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract The purpose of this study was to determine the effect of the school environment on economic motivation in class X SMA Santa Maria Nanga Pinoh. The research method used was descriptive statistics, a form of relation was study research. with a sample of 34 students . Data collection technique were direct observation or field techniques. Data collection tools in this study were questionnaires, observation sheets, interview guides and photos. The results of the study showed that: 1) The school environment was in a very high category with a percentage of 82.70%. 2) The learning motivation of students in class X IIS is in the very high category with a percentage of 82.82%; and there was a positive and significant relationship between the school environment and learning motivation. With the magnitude of the regression value or influence (R) that was equal to 0.666 strong categories. The results of the coefficient of determination (R2) of 0.444 means the percentage contribution of the influence of the school environment on learning motivation of students was 44.4% while the remaining 55.6% is influenced by other factors not examined in this study . In this study the influence of the school environment on learning motivation was categorized very goodKeywords: Economy Lesson, Learning Motivation, School environment,